Using Computer-Assisted Supervision in Counsellor Education Programs - Lehr, Ron (Canadian Journal of Counselling and Psychotherapy, 2007)
The current paper uses information obtained from teaching practices to conceptualize how computers might be used to enhance the supervision of graduate counselling students (herein called beginning counsellors). Using Hill and O’Grady’s (1985) list of counsellor intentions, the author devised a computer program called Counsellor Assisted Supervision that allows beginning counsellors to monitor and evaluate counselling video tapes. The paper provides a description of the computer program, how it can be used in the supervision of beginning counsellors, and its value for use in counsellor education programs. Recommendations for supervisory practices are provided.